2015
DOI: 10.1016/j.jcyt.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the immunoregulatory potency of mesenchymal stromal cells by treatment with immunosuppressive drugs

Abstract: The use of treated MSCs may achieve clinical end points not reached with untreated MSCs and allow for infusion of fewer cells to reduce costs and minimize potential side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…Some studies have indicated that rapamycin, an immunosuppressive drug, could enhance the immunoregulatory potency of pretreated MSCs through subsequent diffusion into cocultures [38]. We showed a similar result in the rapamycin group; however, this result may have been caused by the elevated autophagy level of MSCs.…”
Section: Discussionsupporting
confidence: 70%
“…Some studies have indicated that rapamycin, an immunosuppressive drug, could enhance the immunoregulatory potency of pretreated MSCs through subsequent diffusion into cocultures [38]. We showed a similar result in the rapamycin group; however, this result may have been caused by the elevated autophagy level of MSCs.…”
Section: Discussionsupporting
confidence: 70%
“…A high dose of CyA can then be used to overcome this. In contrast, several studies have reported various synergistic tolerogenic effects of MSCs and immunosuppressive drugs [404][405][406][407] . We therefore combined DSCs and CyA or SRL in MLRs, and measured proliferation between days 5 and 6 of incubation.…”
Section: 360mentioning
confidence: 99%
“…Some studies suggested that MSC can act as drug delivery system. In a recent report it has been shown the capacity of a brief exposure to immunosuppressive drugs to improve the immunoregulatory potency of MSC [27]. In our model, the results suggest that BM-MSC from MPN patients with JAK2V617F mutation does not act as a carrier of the inhibitor but as a specific target for PCI34051.…”
Section: Discussionmentioning
confidence: 64%